Dietary phytase supplementation during peak egg laying cycle of White Leghorn hens on nutrient utilization and functional gene mRNA expression in duodenum and kidney. Issue 6 (2nd November 2019) - Shet, Divya; Ghosh, Jyotirmoy; Ajith, Sreeja; Awachat, Vaibhav Bhagwan; Bhat, Karthik Subramanya; Gowda, Nisarani Kollurappa Shivakumar; Pal, Dintaran; Elangovan, Arumbackam Vijayarangam
ABSTRACT: Seventy-five White Leghorn hens during peak egg laying cycle were randomly divided into 5 groups: 1 group with 0.32% NPP (control), 2 groups with 0.24% NPP and laboratory (T1) or commercial (T2) phytase (250 FTU/kg feed), and 2 groups with 0.16% NPP and laboratory produced (T3) or commercial (T4) phytase (500 FTU/kg feed) from 23 to 40 weeks of age. The results indicated T2 group had the lowest (P > 0.05) bone ash, followed by similar ash content in T1, T3 and control groups. Mineral concentration (Ca, P, zinc and manganese) in the bone was not affected (P > 0.05) by variation in dietary phytase and NPP level. In duodenum, NaPiIIb was up-regulated (P < 0.05) in T2 and T3, whereas Calbindin 1 (CALB1) was up-regulated (P < 0.05) only in T3. In kidney, expression of NaPiIIa and CALB1 were down-regulated (P < 0.05) in all groups. The data demonstrated that 250 FTU/kg laboratory phytase supplementation in feed was enough for replacing 50% of inorganic P and 500 FTU/kg commercial phytase capable of replacing 100% of inorganic P. The up-and down-regulation of NaPiIIb, NaPiIIa and CALB1 genes in treatment groups was independent of phytase source and NPP level in feed.